Does the disclosure of internal control deficiency matter for accrual quality? Evidence from China. Issue 1 (April 2022) - Deng, Kebin; Hu, Fang; Tian, Gary Gang; Zhong, Ziying
Highlights: This paper indicates relative to voluntary ICD disclosure, mandatory ICD disclosure is associated with poorer accrual quality, suggesting that the mandated disclosure of ICD effectively identifies financial reporting quality in Chinese firms. We find that the effectiveness of mandatory ICD disclosure is stronger when firms are controlled by the government (especially when controlled by the central government), when government inspections are more intensive and in less developed regional markets. Our findings contribute to the debate on the effectiveness of disclosure regulations and improve our understanding of internal controls in emerging markets. Abstract: Using a sample of Chinese listed firms that are required to audit and disclose any internal control deficiency (ICD), this paper examines the effect of mandatory ICD disclosure on accrual quality (AQ) in China. We find that relative to voluntary ICD disclosure, mandatory ICD disclosure is associated with poorer AQ, as proxied by abnormal accruals, suggesting that the mandated disclosure of ICD effectively identifies financial reporting quality in Chinese firms. This relationship is enhanced by government control of firms (especially the central government) and by the intensity of government inspections and is stronger in undeveloped regional markets. The results are robust to the application of the PSM-DID method and use of different measures and samples. Our findings demonstrate the critical role of the mandated disclosure of ICD and improve our understanding of internal control mechanisms in emerging markets.